Lichen planus with IgA vasculitis: a rare association - Chalumuru, Shivani; Gopal, K. V. T.; Krishnam Raju, P.V.; Rekha Rani, B. (International Journal of Research in Dermatology, 2022)
Lichen planus is an inflammatory skin disorder which has been shown to be associated with thyroid disorders, hepatitis B, hepatitis C. IgA vasculitis is a form of cutaneous small vessel vasculitis (CSVV) characterized by palpable purpura, abdominal pain and joint pain usually seen in children. We report a case of 45-year-old female patient came with violaceous itchy lesions which were distributed over trunk and extremities of 1 month duration. Complete blood count (CBC) and serum biochemistry tests were normal. Histopathology of violaceous lesions showed changes of lichen planus. Purpuric lesions showed mild perivascular and transmural inflammatory infiltrate, composed mainly of neutrophils and few lymphocytes in the superficial dermis. Direct immunofluorescence was positive for IgA (granular pattern along with vessel walls of small vessels). Based on clinical, histopathological findings, a diagnosis of lichen planus with IgA vasculitis was made. The patient was treated with 30 mg prednisolone, gradually tapered over 6 weeks and anti-histamines. Satisfactory response was observed at follow-up at 6 weeks. Our case highlights the rare association of lichen planus with IgA vasculitis. Thorough evaluation of the patient helped in reaching correct diagnosis.